Kebijakan Hukum Daerah Tentang Pengelolaan Parkir: Problematika dan Solusinya di Kota-Kota Besar - Maroji, Maroji; Samad, Izzan Firizqi Abdul; Puannandini, Dewi Asri (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze regulations regarding the management of Hazardous and Toxic Materials (B3) waste in Indonesia, specifically regarding the safe and sustainable storage, retention, and disposal of B3 waste. Furthermore, this study also provides the effectiveness of sanctions against violations in the industrial sector and healthcare facilities to assess the regulation's ability to reduce environmental pollution and its impact on public health. This study uses a normative juridical method with a descriptive approach, focusing on the analysis of laws and legal doctrines. Based on the analysis, it was found that although the regulations have been clearly regulated, various challenges remain in their implementation, such as weak supervision, complex licensing processes, and low business awareness. Therefore, strategies are needed to improve technology-based supervision, reform the licensing system, impose sanctions, provide incentives for compliant industries, and increase public participation. The findings and recommendations in this study can be a real contribution to strengthening a more effective, firm, and sustainable B3 waste management system, in order to support environmental protection and public health.